2019
DOI: 10.1175/jcli-d-18-0700.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Land Surface Effects on the Moisture Transport over South America with a Moisture Tagging Model

Abstract: Land–atmosphere interactions are a critical component of precipitation processes within the Amazon basin and La Plata River basin (LPRB) in South America. Two of the possible pathways through which the land surface can affect precipitation are 1) by changing the amount of moisture available for precipitation (moisture recycling) and 2) by changing the atmospheric thermal structure and consequently affecting circulation patterns. In this study, the Weather Research and Forecasting (WRF) Model with embedded wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 58 publications
5
42
0
Order By: Relevance
“…There exists a preference for initial deep convective cells to be triggered near the foothills of the Andes close to Sierra de Cordoba in Argentina (e.g., DCCs shown in Figure 5F), under a strong topographically-driven convective initiation and maintenance. Although the Amazonian moisture source for the SALLJ does not seem to be as significant as originally thought (Yang and Dominguez, 2019), it is sometimes capped by leeside subsidence of the midlevel dry air that flows over the Andes from the eastward synoptic disturbances. The breaking of this cap triggers the release of convective instability and deep convection leading to tornadoes, hail and floods along the plains between the Andes and the Atlantic coast (Grandoso, 1966;Nascimento and Marcelino, 2005;Matsudo and Salio, 2011;Rasmussen and Houze, 2011;Mezher et al, 2012;Rasmussen et al, 2014).…”
Section: Extratropical Andesmentioning
confidence: 78%
“…There exists a preference for initial deep convective cells to be triggered near the foothills of the Andes close to Sierra de Cordoba in Argentina (e.g., DCCs shown in Figure 5F), under a strong topographically-driven convective initiation and maintenance. Although the Amazonian moisture source for the SALLJ does not seem to be as significant as originally thought (Yang and Dominguez, 2019), it is sometimes capped by leeside subsidence of the midlevel dry air that flows over the Andes from the eastward synoptic disturbances. The breaking of this cap triggers the release of convective instability and deep convection leading to tornadoes, hail and floods along the plains between the Andes and the Atlantic coast (Grandoso, 1966;Nascimento and Marcelino, 2005;Matsudo and Salio, 2011;Rasmussen and Houze, 2011;Mezher et al, 2012;Rasmussen et al, 2014).…”
Section: Extratropical Andesmentioning
confidence: 78%
“…Today and in the mid-Holocene the central and western Amazon sits inland from the primary moisture source-the easterly trade winds that cross the Atlantic Ocean [93,94]-so precipitation is strongly dependent on upstream moisture recycling. About one-third to half of all precipitation in this region is derived from evapotranspiration within the basin today [58,57,95,96], making it particularly sensitive to feedbacks like the MRF that can promote forest-grassland transitions [42,97,58,57,35,98,47].…”
Section: Mid-holocene Climatementioning
confidence: 99%
“…Additionally, some studies have shown that the increase/decrease in precipitation over La Plata and southern South America is related to the crucial role of the Amazon basin as a source of moisture for precipitation in the southern regions of the continent. 50,51 Reportedly, under the influence of El Niño, a decrease in precipitation is usually observed in the northeast of South America. Under the influence of La Niña, which always modulates precipitation of oceanic origin that is the most important source of precipitation in the tropical north and south Atlantic Ocean, an increase in precipitation is usually observed.…”
Section: Discussionmentioning
confidence: 99%